Evaporative cooling systems for swine - Nichols, David A.; Ames, D.R.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials involving 168 finishing pigs were conducted to compare continuous fogging with intermittent wetting to reduce heat stress in swine. In the second trial, intermittent wetting by sprinklers (1 min. sprinkle, 29 min. dry) significantly improved (P<.05) average daily gain and average daily feed over control, yet no significant differences in feed to gain ratios were observed between controls and fogged pigs in the second trial.
Keywords: Swine; Evaporative cooling systems